Flue gas purification from SO2 and NOx using molten mixture of alkali metal carbonates. Issue 10 (3rd October 2022) - Dosmukhamedov, Nurlan; Kaplan, Valery
ABSTRACT: Sulfur dioxide (SO2 ) and nitrogen oxides (NOx ) in flue gas are a hazardous atmospheric pollutant associated with coal combustion and non-ferrous metal production. Here we report that laboratory pilot unit for scrubbing of industrial flue gas containing 80 ± 2 ppm SO2 followed by melt regeneration with either CO or natural gas, verified that only 1.5–2.0 ppm SO2 remained in the flue gas. The tests with the semi-industrial scale unit (271.26 kg of the eutectic carbonate melt and flue gas containing 0.15% SO2, 13 ppm NO, 52 ppm NO2 ) were received. In all tests, sulfur extraction from flue gas to the carbonate melt was >90–95% and nitrogen oxides extraction from flue gas to the carbonate melt was 60%. Sulfur and nitrogen oxides extraction from carbonate–sulfate–nitrite melt during regeneration stage was >99%. Carbonate melt-based SO2 scrubbing therefore represents a practical and economical method for limiting sulfur and NOx emission to the atmosphere from both coal-firing power stations and non-ferrous metallurgical processing plants.